Experimental study on effect of use of oxyhydrogen blends with traditional fuels in spark engines for better performance - Erdemir, Dogan; Dincer, Ibrahim; Patel, Dipal (ELSEVIER, 2024)
The utilization of oxyhydrogen as a supplementary fuel in internal combustion engines has garnered significant attention due to its potential to enhance engine performance and reduce emissions. This study investigates the effects of oxyhydrogen addition on the performance, emissions, and thermodynamic efficiencies of a sparkignition engine fueled by gasoline, propane, and methane. The engine drives a commercial stationary power generator. The results demonstrate that oxyhydrogen addition leads to a consistent reduction in CO2 and hydrocarbon emissions across all fuel types, with the most substantial reduction observed in gasoline, decreasing from 2413 g/kg to 1709 g/kg (a 29 % reduction) with 20 % oxyhydrogen addition. However, NOx emissions tend to increase, particularly pronounced in gasoline, where they escalate from 9.5 g/kg fuel with no oxyhydrogen to 24.6 g/kg fuel for the same case (a 159 % increase). The power output exhibits varying degrees of improvement depending on the fuel type and oxyhydrogen concentration. Oxyhydrogen has compensated for the power reduction when propane and methane are used as the base fuel. The energy and exergy efficiencies consistently improve with increasing oxyhydrogen addition, with the most significant improvement observed in propane, where the energy efficiency increases from 30.0 % to 37.3 % with and addition of 20 % oxyhydrogen.
Keywords: Oxyhydrogen; Hydrogen; Methane; Propane; Combustion; Emission; Spark engine; Power generator; DIRECT-INJECTION ENGINE; NATURAL-GAS; EMISSIONS; EXERGY; Engineering